El control interno y su incidencia en el cumplimiento de objetivos y metas en la cooperativa de ahorro y crédito "9 de Octubre Ltda - Hidalgo Guanoluisa, Mónica Alexandra (2019)
Today's financial institutions require Internal Control as it is essential in different departments, areas and activities, while at the same time they are necessary for the administration, and its staff to achieve the institutional ideals, because each person from its department will have to achieve the established functions and giving the added value to demonstrate the capacities and competences in its jobs, for that reason this research was carried out at "Cooperativa de Ahorro y Crédito 9 de Octubre Ltda., taking into account that the Institution has Internal Control which has allowed it to partially achieve its purposes such as: improve the satisfaction level of shareholders and customers, properly manage the client portfolio, create new products and services, this being the main problem for the research development; That is why the objective analyzed the Internal Control system to determine its impact on the objectives achievement and goals in the business area of the institution, where documentary research was applied through the use of books, articles allowing the support of the theoretical framework; field research was also used by a structured interview and an internal control questionnaire based on COSO II which contributed to the analysis of the context in the business area, diagnosing the achievement of its purposes. As a result, internal control affects the achievement of the institutional objectives established in the strategic plan, since these control systems must be designed to achieve them; Therefore, it is concluded that certain shortcomings in the analysis of external and internal factors would affect the objectives achievement, policies and procedures for the activities performance; the results obtained through the Internal Control evaluation will contribute to the decision making of Management as Legal Representative; also the Management levels at “Cooperativa de Ahorro y Crédito “9 De Octubre Ltda” that play an important factor in the provisions issued, who will be the direct beneficiaries of this research